Utilization of Natural Products as Functional Feed - Magdalena, Stella; H, Natadiputri G; F, Nailufar; T, Purwadaria (Indonesian Animal Sciences Society, 2013)
The use of antibiotics as feed additive improves performance in livestock. However, scientific data related to the use of antibiotics in feed merge spreading of bacterial resistance in animal and human bodies, therefore the usage of antibiotics in animal production is restricted. This condition raise the utilization of natural antibiotic as functional feed such as phytogenics (essential oil, flavonoid, saponin, and tannin), enzyme, probiotic, and prebiotic to improve the livestockâs performance, quality, and health. Functional feeds increase profitability in animal husbandry production and its use is feeds are expected to be functional foods that may have positive effects in human nutrition. Key words: Functional feed, phytogenic, enzyme, probiotic, prebiotic